2016
DOI: 10.1007/s11695-016-2273-2
|View full text |Cite
|
Sign up to set email alerts
|

Low Educational Status and Childhood Obesity Associated with Insufficient Mid-Term Weight Loss After Sleeve Gastrectomy: a Retrospective Observational Cohort Study

Abstract: Childhood obesity and a lower level of education are associated with insufficient weight loss 6 months after SG. However, prospective external validation is warranted, with a long-term follow-up of a large bariatric surgery population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Psychological and socioeconomic behaviour has been already welldiscussed in literature [6,16,24,25]. To our knowledge, no data were available about grazing as predictor of IWL but consistent literature identified this disorder as a predictor of weight regains [20].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Psychological and socioeconomic behaviour has been already welldiscussed in literature [6,16,24,25]. To our knowledge, no data were available about grazing as predictor of IWL but consistent literature identified this disorder as a predictor of weight regains [20].…”
Section: Discussionmentioning
confidence: 94%
“…Several authors considered excess weight loss percentage (EWL%) the most practice parameter to evaluate IWL [3,5,6]. Although patients presented a great EWL heterogeneity, Reynaud criteria defined unsatisfactory results as EWL lower than 50% [7], and literature defined IWL as EWL<50% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Underlying comorbidities, including diabetes, high blood pressure, hyperlipidemia, and elevated levels of serum HbA1c and triglycerides, are recognized as risk factors for weight loss failure (55,47,60).…”
Section: ) Underlying Disease and Comorbidity Associationsmentioning
confidence: 99%
“…In individuals with obesity surgery, it is important to maintain an ideal weight for a long time after surgery. It has been found that postoperative feeding behavior and psychological and sociocultural characteristics have an effect on achieving ideal weight loss or maintaining body weight after surgery (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%